À propos de l’intérêt de questionner l’activité improvisationnelle des jeunes enseignants - Guillaume Azéma; Serge Leblanc (Recherches en Éducation)
Within the framework of a situated cognitive anthropology, our research focuses on the description-understanding of new teachers’ improvisational activity, in class as a dynamic environment. We will try to clarify how they improvise, when they think they are improvising. We view improvisation as a crucial space of self-creation, as well as a process which could bring to light a dimension of the activity still little taken into account in professional development though and tutoring reflexions.